"Non‐Financial" Is a Misnomer, but Doesn't Have to Be a Missed Opportunity. Issue 2 (10th June 2020) - Glazerman, Gail; Cohen, Jeff
Abstract : With enterprise values now representing increasing multiples of companies' net book assets, investors are clearly looking beyond financial reporting for enhanced insights and understanding of when and how companies are adding value. This shift includes growing attention to environmental, social, and governance (ESG) information. Although ESG data presents its own unique challenges, dismissing it as "non‐financial" can be misleading. When explicitly linked to a company's long‐term value creation strategy, ESG information can serve as a valuable input to more farsighted financial analysis. Market‐driven initiatives, notably that of the Sustainability Accounting Standards Board (SASB), aim to standardize a subset of business‐critical, industry‐specific sustainability data for investors. Research indicates such approaches can generate positive outcomes not only for providers of financial capital, but for their portfolio companies and markets in general. In illustrating these concepts, the authors explore ESG impacts in three sectors and industries, while examining how access to consistent, comparable, reliable sustainability information in those sectors can augment an analysis of traditional business fundamentals. One example focuses on water management in the Oil & Gas Exploration & Production industry, a major environmental issue where geographic considerations can shed light on company‐specific exposures to cost increases, production disruptions, increased CapEx and R&D spending, as well as the potential for asset write‐downs. In the Food & Beverage sector, health and nutrition concerns are shown to be changing consumer preferences, triggering regulatory action, and reshaping companies' product portfolios—with significant implications for the companies' brand values and ability to compete for market share. Finally, in Aerospace & Defense, lapses in business ethics such as bribery of government officials present a governance challenge that comes with the risk of value‐destroying fines and penalties and, even more significant, associated reductions in revenues.